STAT3 as a critical target of Sijunzi Decoction in the treatment of gastric cancer: evidence from integrated network pharmacology and experimental validation - Luo, XiaoYu; Xie, GuiPing; Tan, QianYing; Wang, YaoHui; Wang, HaiDan; Zhai, Jing (Frontiers in Molecular Biosciences, 2025)
BackgroundGastric cancer (GC) is an importent cause of global cancer mortality, underscoring the need for therapeutic strategies. Traditional Chinese medicine (TCM), particularly Sijunzi Decoction (SJZD), has demonstrated clinical promise as an adjuvant therapy in oncology by improving survival and reducing chemotherapy toxicity. However, the mechanistic basis of SJZD’s anti-tumor activity, especially concerning its potential immunomodulatory effects within a competent tumor microenvironment, remains poorly elucidated due to the complexity of its components and limitations of previous preclinical models.MethodsThe subcutaneous tumor models were established in inbred 615 mice with MFC cells, and RNA-sequencing (RNA-Seq) was performed on tumor tissues to characterize treatment-associated differentially expressed genes across three groups (model, early Sijunzi Decoction, and synchronization Sijunzi Decoction). Network pharmacology analysis predicted the bioactive compounds and putative targets of Sijunzi Decoction, and constructed a compound-target-disease network to explore potential GC-related pathways. The expression profile of STAT3 in gastric cancer tissues from three groups of mice model was examined through Western blotting assays and immunohistochemistry to determine its role in Gastric cancer and its regulatory relationship.ResultsSJZD could prevent tumor growth. Additionally, the earlier Chinese medicine intervention, the more definiter tumor inhibition. The RNA-Seq revealed an immunomodulatory gene signature, as evidenced by the 13 common DEGs significant enrichment in the JAK-STAT pathway. Network pharmacology identified 156 overlapping targets between SJZD and GC, among which STAT3 was recognized as a critical hub gene. Forthermore, Western blot and IHC analysis confirmed that SJZD had downregulated STAT3 protein expression in tumor tissues.ConclusionSJZD had a definitely inhibitive effect against GC in mice by regulation the STAT3 expression in JAK/STAT signaling pathway, providing a mechanistic rationale for the potential clinical translation of SJZD in GC treatment.